Association between clinical experience and antibiotic prescription by dentists in cardiac disease patients undergoing root canal treatment - Amjad, Zain; Jabbar, Maria; Zafar, Quratul-Ain; Abdullah, Syed Muhammad; Imtiaz, Hira; Kanwal, Namra (Infectious Diseases Journal of Pakistan, 2024)
Background: The microorganism present in the oral cavity have been reported previously to cause opportunistic infections in cardiac disease patients. This is the reason why antibiotic prophylaxis is considered very essential for these patients before undergoing dental treatment. The objective of the study is to find the association between clinical experience of dental practitioners and use of antibiotic prescription in cardiac disease patients undergoing root canal treatment. Material and Methods: A cross-sectional study was conducted on 100 dentists in Sharif Medical and Dental college, Lahore over a period of one year. Data was collected through a questionnaire that collected information on trends of antibiotic prescription of dentists for cardiac disease patients (Infective Endocarditis patients, Myocardial Infarction patients and prosthetic heart valve patients) undergoing root canal treatment. All dental practitioners working in clinical sciences irrespective of their age and gender were included in the study. Those with a clinical experience of less than 6 months were excluded from the study. Results: A statistically non- significant association between clinical experience and antibiotic prescription trends of among dental practitioners for myocardial infarction patients (p=0.265), Infective Endocarditis patients (p=0.119), Prosthetic heart valves (p=0.062) undergoing root canal treatment. Conclusion: Dental practitioners with experience of more than 3 years tended to prescribe antibiotics to high-risk patients more than those with a lesser clinical experience. Keywords: Antibiotic prescription, Cardiac disease patients, Dental practitioners, Oral infection, Root canal treatment